Progress in Wall Turbulence: Understanding and Modeling Proceedings of the WALLTURB International Workshop held in Lille, France, April 21-23, 2009 - Stanislas, Michel; Jimenez, Javier; Marusic, Ivan.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2011)
This book brings together selected contributions from the WALLTURB workshop on (3y(BUnderstanding and modelling of wall turbulence(3y (Bheld in Lille, France, on April 21st to 23rd 2009. This workshop was organized by the WALLTURB consortium, in order to present to the relevant scientific community the main results of the project and to stimulate scientific discussions around the subject of wall turbulence. The workshop reviewed the recent progress in theoretical, experimental and numerical approaches to wall turbulence. The problems of zero pressure gradient, adverse pressure gradient and separating turbulent boundary layers were addressed in detail with the three approaches, using the most advanced tools. This book is a milestone in the research field, thanks to the high level of the invited speakers and the involvement of the contributors and a testimony of the achievement of the WALLTURB project.s
Invited speakers -- Session 1: The WALLTURB LML Experiment -- Session 2: Experiments in Flat Plate Boundary Layers -- Session 3: Experiments in Adverse Pressure Gradient Boundary -- Session 4: Boundary Layer structure and scaling -- Session 5: DNS and LES -- Session 6: Theory.-Session 7: RANS modelling -- Session 8: Dynamical systems -- Session 9: Large Eddy Simulation -- Session 10: skin friction -- Session 11: Modified wall flow -- Session 12: Industrial modeling.
Keywords: Engineering; Computer science; Hydraulic engineering; Engineering; Engineering Fluid Dynamics; Fluid- and Aerodynamics; Automotive Engineering; Computational Science and Engineering